2015
DOI: 10.1186/s13000-015-0245-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HNF-1β in cervical carcinomas: an immunohistochemical study of 155 cases

Abstract: BackgroundHNF-1β is a commonly used marker in the differential diagnosis of clear cell carcinoma of the ovary and endometrium. Recent studies have found HNF-1β expression to a lesser extent in other ovarian and endometrial tumors including endometrioid, mucinous and, rarely, serous carcinoma. Regarding cervical carcinoma, HNF-1β expression has been mentioned exceptionally in mesonephric and some other types of adenocarcinoma. However, a systematic analysis of HNF-1β expression in cervical carcinomas has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
2
5
1
Order By: Relevance
“…The difference of HNF-1β expression between cervical SCC and adenocarcinoma was statistically significant (p < 0.001). This is close to study by Němejcová et al [13].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The difference of HNF-1β expression between cervical SCC and adenocarcinoma was statistically significant (p < 0.001). This is close to study by Němejcová et al [13].…”
Section: Discussionsupporting
confidence: 74%
“…We assessed and graded the stained slides based on the percentage of stained cells as; one = 5-30 percent; two = 31-60 percent; three > 60 percent & zero < 5 percent of positive cells, the intensity of HNF-1β stain as weak one, moderate two or strong three [13]. We calculate the total final from zero to nine by multiplying the intensity values by the percentages of positive cells; we consider the final cut-off point is four above which considered high-expression and below which was considered low-expression of the marker.…”
Section: Evaluation Of Hnf-1β Protein Expressionmentioning
confidence: 99%
“…In the current study, HNF1β was positive in 13 of 14 (93%) tumours tested and although immunoreactivity was weak in a number of cases, it was almost always diffuse. In another study, 42 of 56 (75%) cervical adenocarcinomas exhibited positive nuclear staining with HNF1 β but the morphological subtypes were not detailed (31). Given that some clear cell carcinomas are only weakly positive with HNF1β, this marker is of no value in distinguishing gastric-type adenocarcinoma from clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…In tumors, mutations and epigenetic inactivation of the HNF-1β gene has been shown to be involved in the development of several cancers [1517]. Recently, it has been reported that the expression of HNF-1β in cervical carcinoma is mostly restricted to adenocarcinomas and can be used as an auxiliary adenocarcinoma marker in the differential diagnosis of poorly differentiated cervical carcinomas [18]. However, the expression and precise role of HNF-1α (HNF1A) in carcinogenesis as well as the importance of molecular targeting of this protein for therapeutic purposes remains unknown.…”
Section: Introductionmentioning
confidence: 99%